2017
DOI: 10.18632/oncotarget.15977
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of HPV16 gene expression profiles in cervical and in oropharyngeal squamous cell carcinoma

Abstract: Human papillomavirus type 16 (HPV16) is the major cause of cervical cancer and of a fraction of oropharyngeal carcinoma. Few studies compared the viral expression profiles in the two types of tumor. We analyzed HPV genotypes and viral load as well as early (E2/E4, E5, E6, E6*I, E6*II, E7) and late (L1 and L2) gene expression of HPV16 in cervical and oropharyngeal cancer biopsies. The study included 28 cervical squamous cell carcinoma (SCC) and ten oropharyngeal SCC, along with pair-matched non-tumor tissues, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 80 publications
3
29
0
Order By: Relevance
“…Genomic DNA was extracted from approximately 10 mg of fresh frozen tissues and 5 × 10 6 cultured cells by digestion with proteinase K (150 μg per mL at 37°C for 10 hr) in 100 μL of lysis buffer (10 mM Tris–HCl pH 7.6, 5 mM EDTA, 150 mM NaCl, 1% SDS), followed by extraction with phenol–chloroform–isoamyl alcohol (25:24:1) and ethanol precipitation in 0.3 M sodium acetate (pH 4.6) . DNA was extracted from paraffin embedded tissues as described previously .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from approximately 10 mg of fresh frozen tissues and 5 × 10 6 cultured cells by digestion with proteinase K (150 μg per mL at 37°C for 10 hr) in 100 μL of lysis buffer (10 mM Tris–HCl pH 7.6, 5 mM EDTA, 150 mM NaCl, 1% SDS), followed by extraction with phenol–chloroform–isoamyl alcohol (25:24:1) and ethanol precipitation in 0.3 M sodium acetate (pH 4.6) . DNA was extracted from paraffin embedded tissues as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…TERT expression levels were evaluated by real‐time PCR using forward (5′‐CGGAAGAGTGTCTGGAGCAA‐3′) and reverse (5′‐GGATGAAGCGGAGTCTGGA‐3′) primers targeting TERT exon 3 and exon 4, respectively, which encompassing the intron 3 allow to exclude cross contamination of cDNA with genomic DNA. The samples have been analyzed previously for HPV16 early (E2/E4, E5, E6, E6*I, E6*II, E7) and late (L1 and L2) transcripts by real‐time PCR . The reaction mixtures included 12.5 μL of 1× iQ SYBR Green supermix (Bio‐Rad Laboratories Inc., Hercules, CA), 10 pmol of each primer, 1 μL of cDNA and nuclease‐free water in a final volume of 25 μL.…”
Section: Methodsmentioning
confidence: 99%
“…This result may reflect the higher proliferation rate of HPV-infected cells from COMC compared to CSOM and NME, suggesting that viral DNA replication may occur in COMC. It has been reported that HPV infection leads to the expression of the viral oncoproteins E6 and E7, which stimulate cell growth and viral DNA replication [22,[33][34][35][36][37]. Although no studies are available on HPV DNA load in normal and pathological middle ear tissues, our results are in agreement with previous uterine cervix investigations reporting a mean of viral DNA copy/cell ranging from 0.1 to 18 in cervical intraepithelial neoplasia and less than one viral DNA copy/cell in normal cervical tissues [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of risk factors, pathogenesis as well as in prognosis, OPSCC can be subdivided into two groups: HPV‐positive and HPV‐negative tumours. Particularly, the high‐grade HPV type 16 was shown to induce cancers of the cervix and head and neck region—especially OPSCC . HPV‐negative OPSCC are frequently associated with consumption of tobacco and alcohol, cause less lymphatic metastasis, and were shown to have a worse prognosis in comparison with HPV‐positive OPSCC .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, LNR incorporates the information of extension of neck dissection as well as the number of positive lymph node metastases, which is not included in the UICC/ AJCC TNM classification concept in detail.In terms of risk factors, pathogenesis as well as in prognosis, OPSCC can be subdivided into two groups: HPV-positive and HPV-negative tumours. Particularly, the high-grade HPV type 16 was shown to induce cancers of the cervix and head and neck region-especially OPSCC 2,[17][18][19]. HPV-negative OPSCC are frequently associated with consumption of tobacco and alcohol, cause less lymphatic metastasis,…”
mentioning
confidence: 99%